Effects of Different Numbers of Trials on Saccadometry Test Results - Aysenur Kucuk Ceyhan; Asya Fatma Men; Zahra Polat (Brain and Behavior, 2025)
ABSTRACT Purpose The aim of this study was to investigate the effect of the number of trials on the recording in the saccadometry test. Method Forty‐five healthy participants (mean age ± SD = 25.89 ± 5.2 years) (31 female and 14 male) aged 19–40 years were included in the study. Each participant underwent two saccadometry tests, first a test protocol with 100 trials and then a test protocol with 60 trials, administered by the same experienced clinician, one hour apart. All test settings remained constant between the two test sessions, with the exception of the number of trials. Results With 100 trials, antisaccades had a much higher mean latency (paired samples t‐test; t = 4.838; p = 0.0001 < 0.01), directional error rate (Wilcoxon signed ranks test; Z = −1.991; p = 0.047), and overall error rate (Wilcoxon signed rank test; Z = −2.207; p = 0.027) compared to the results obtained from the test protocol with 60 trials. There was no significant difference in mean velocity or accuracy (Wilcoxon signed rank test; p > 0.05). The prosaccades, mean latency, velocity, directional error, and overall error (Wilcoxon signed ranks test; p > 0.05) and mean accuracy (paired samples t‐test; p > 0.05) did not differ between 100 and 60 trials. Conclusion The decline in antisaccade performance with an increasing number of trials may be attributed to the disruptive effect of mental fatigue on the inhibition process. Further research is required to investigate the relationship between mental fatigue and the inhibition process in the context of antisaccade function.